Keberlakukan Daftar Negatif Investasi, Kasus: Intervensi Qatar Telecom di Indonesia - Velentina, Rouli Anita; Hayaty, Lydya (UI Scholars Hub, 2009)
Improving legal certainty to attract foreign investment is very significant because it is one of very important consideration which involved in the decision to choose where to invest. In relation to legal certainty, an issue that has being discussed intensively is the investment conducted by Qatar Telecom, a big company form Middle East and a shareholder of PT. Indosat Tbk. The legal issue which arise is, Qtel would like to buy Indosat shares and increase its shares in PT. Indosat to be more than 50%. However under Presidential Regulation No. 111/2007, the maximum of foreign capital ownership limit in the business sector of telecommunication was 49%. Then, Ministry of Economic Coordinator concluded for any company that had been invested before the enactment of Presidential Regulation No. 111/2007 was governed by existing Negative List of Investment at the time the company established. This article analyzes the enforcement of Negative List of Investment regulated in Presidential Regulation No.111/2007 to the investment in the capital market.